2022
DOI: 10.1002/tox.23689
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B complex blocks the dust fall PM2.5‐induced acute lung injury through DNA methylation in rats

Abstract: This study aimed to explore whether vitamin B complex (folic acid, B 6 , and B 12 ) could avert DNA methylation changes associated with inflammation induced by acute PM 2.5 exposure. Sprague-Dawley rats were administered by gavage with different concentrations of vitamin B complex once a day for 28 days, and then by intratracheal instillation with saline or PM 2.5 once every 2 days for three times. Vitamin B continued to be taken during the PM 2.5 exposure. Rats were sacrificed 24 h after the last exposure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Bai et al. [ 31 ] performed a study with different concentrations of B vitamins including vitamin B6 and found that the B vitamins could block lung injury from exposure to toxins and even regulate expression on the level of transcription to protect against insults to the lung [ 31 , 32 ]. In 1984, Moriguchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al. [ 31 ] performed a study with different concentrations of B vitamins including vitamin B6 and found that the B vitamins could block lung injury from exposure to toxins and even regulate expression on the level of transcription to protect against insults to the lung [ 31 , 32 ]. In 1984, Moriguchi et al.…”
Section: Discussionmentioning
confidence: 99%